Hegemoni dalam Novela Hidup Ini Brengsek dan Aku Dipaksa Menikmatinya Karya Kolaborasi Antara Puthut Ea Dan Gindring Wasted - Novi Aryanti; Ferina Meliasanti (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study is focused on revealing the elements of Gramsci's hegemony contained in the novels, Life Is Fuck and I Was Forced to Enjoy It. The method used in this research is descriptive qualitative, listening technique and note-taking technique. The approach used in this research is the sociology of literature approach which is focused on Gramsci's theory of hegemony. Gramsci's theory of hegemony is a concept to understand political, cultural, and ideological forms that are considered to have the power to reform society. The technique used in this research is literature study and documentation study. The subject of this research is the novela Life Is Fuck And I Was Forced To Enjoy It, while the object of the research is the element of hegemony contained in the literary work. The results showed that there were elements of hegemony that emerged, namely ideological hegemony, power hegemony, cultural hegemony, moral hegemony, and economic hegemony. And the way the author describes the story of the main character in the novel